Establishing the validity of “Sports Talent®”: a methodology for motor talent detection in sports - Michael Douglas Celestino Bispo; Marcos Antonio Almeida-Santos; Antonio Carlos Gomes; Márcio Duarte Carvalho Alves; Estélio Henrique Martins Dantas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The objective of the study was to establish the scientific validity of a comprehensive methodology for motor talent detection in sports, named “Sports Talent®”. The methodology was created and validated through the Delphi method, with the participation of expert evaluators with expertise in High Performance Sport (HPS). The proposed structure of the method was submitted to an Expert Evaluator Panel (QPA), initially consisting of 90 participants, of whom 23 remained until the end of the study. The characteristics of the remaining participants were as follows: age = 44.3 ± 10.5 years; period dedicated to work in HPS: = 12.3 ± 10.4 years. The Delphi method involved formulating questions to obtain responses on a Likert scale, conducted over three rounds. Significant improvements in reliability and agreement among the QPA were noted in each round of the Delphi method. In Round 1, out of 95 sent questionnaires, 43 responses were received, yielding a Cronbach's alpha value of α = 0.72 and a 93.0% agreement rate for the tests. By Round 3, of the 25 questionnaires sent, 23 responses were received, achieving a perfect Cronbach's alpha value of α = 1.0 and a 100.0% agreement rate. The high relevance and consistency of tests such as the Sociocultural Contextual Inventory, Biological Maturation by Tanner, Informatized Dermatoglyphics, Epigenetic Anthropometry, and the Motivation Form were evident across all rounds. The order of procedure execution also showed increasing consensus, highlighting the progressive alignment of expert opinions throughout the study.